1993
DOI: 10.1002/dc.2840090413
|View full text |Cite
|
Sign up to set email alerts
|

Primary mucoepidermoid carcinoma of the thyroid: Diagnosis by fine‐needle aspiration biopsy

Abstract: Fine-needle aspiration biopsy (FNAB) has been recognized as a safe and reliable procedure in the evaluation of thyroid nodules. We herein report a case of a low-grade mucoepidermoid carcinoma of the thyroid that was diagnosed with this technique. Examination of an intra-operative FNAB showed cohesive clusters of polygonal squamoid cells with distinct cellular borders, uniform round nuclei, distinct nucleoli, and homogeneous amphophilic to cyanophilic cytoplasm. Focal keratin "pearl" formation was apparent, alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
3

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 15 publications
0
13
0
3
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10] Fisher et al 15 suggested that the real frequency in the breast is higher that thought since MEC may masquerade under other diagnoses, such as atypical squamous metaplasia, in the context of infiltrating ductal carcinoma. The diagnosis of our case was initially incorrect since in the preliminary cytologic study, the tumor was thought to be a ductal carcinoma associated with atypical squamous metaplasia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10] Fisher et al 15 suggested that the real frequency in the breast is higher that thought since MEC may masquerade under other diagnoses, such as atypical squamous metaplasia, in the context of infiltrating ductal carcinoma. The diagnosis of our case was initially incorrect since in the preliminary cytologic study, the tumor was thought to be a ductal carcinoma associated with atypical squamous metaplasia.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Those locations are extremely rare; the majority have been described as isolated cases. Only 24 cases have been reported to occur in the breast; of them, just one was diagnosed by fine needle aspiration cytology (FNAC).…”
mentioning
confidence: 99%
“…Entretanto, quanto ao CMET, não há certeza sobre a capacidade de produção de TG pelas células tumorais, nem se essas células sejam capazes de captar o radioiodo. De acordo com os casos levantados na literatura, houve positividade para TG em 41% deles, nos quais esse marcador foi utilizado na análise imunohistoquímica (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Discussionunclassified
“…Os autores que utilizaram marcadores neuroendócrinos demonstraram positividade destes marcadores na maioria dos casos (2,8,13). Os resultados com o marcador tireoglobulina (TG) foram divergentes: a maioria dos estudos mostrou negatividade para este marcador nos tumores mucoepidermóides (2,4,10,12,15,17,18,20,23). No entanto, em alguns casos, numa mesma amostra ocorreu positividade para TG nas células foliculares não envolvidas pela neoplasia e negatividade nas células realmente comprometidas (5).…”
Section: Aspectos Histopatológicos E Imunohistoquímicos Do Cmetunclassified
See 1 more Smart Citation